Do Local Elections Affect the Spending of Intergovernmental Transfers? Evidence from Germany's Stimulus Package of 2009 - Yannick Bury; Lars P. Feld (CESifo GmbH, 2024)
In this paper, we study whether local spending of intergovernmental grants is influenced by mayoral elections in the grant receiving municipality. We exploit the implementation of the German federal government's second economic stimulus package of 2009 (K2) in the state of Baden-Wuerttemberg as natural experiment. In the context of this package, all municipalities in Baden-Wuerttemberg received lump-sum grants for local public investment spending. Applying a difference-in-differences and instrumental variables approach to ensure exogeneity of the decision of mayors to run for re-election, we provide evidence that, in the absence of an election, K2 grants led to an increase in a municipality's spending on long-run investment, while municipalities in which the incumbent mayor stood for re-election used grants to increase both, long-run and rapidly visible short-run investment expenditures. Moreover, we provide evidence in favor of the flypaper effect for all municipalities, except for those in which the incumbent mayor did not seek re-election.
Keywords: H30; H72; H77; H81; E61; E62; 330; intergovernmental grants; flypaper effect; political budget cycles